(untitled) (NAU Journal of Technology and Vocational Education, 2025)
In distressed economies characterized by unemployment, inflation, technological disruption, and global uncertainties, employability skills have become critical for fostering workforce resilience and adaptability. This paper explores how competencies such as problem-solving, critical thinking, communication, teamwork, adaptability, and digital literacy enable individuals to withstand economic shocks, navigate job transitions, and sustain career growth in dynamic labour markets. It highlights how economic challenges intensify the demand for workers who can embrace lifelong learning, leverage both soft and technical skills, and adapt quickly to evolving roles. The discussion positions employability skills as survival tools, examining their role in resilience, adaptability and workforce sustainability, while also considering stakeholder perspectives and implications. The paper argues that individuals, employers, and policymakers share a collective responsibility to prioritize skill development in addressing graduate unemployment, bridging skills gaps, and enhancing national productivity. Ultimately, it concludes that deliberate investment in employability skills is essential not only for individual career success but also for sustaining organizational competitiveness and strengthening long-term economic resilience in a volatile global environment.